2010
DOI: 10.1111/j.1349-7006.2009.01388.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant adenovirus encoding vasohibin prevents tumor angiogenesis and inhibits tumor growth

Abstract: Numerous lines of evidence have shown that angiogenesis plays a pivotal role in the development of tumors. Therefore anti‐angiogenesis therapy represents a potentially promising approach to cancer therapy. Recently, a new inhibitor called vasohibin was discovered to operate as an intrinsic and highly specific feedback inhibitor in the process of angiogenesis. However, to date, reports on the antitumor and anti‐angiogenic properties of vasohibin have been very limited. To explore the potential of vasohibin as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
3
19
0
Order By: Relevance
“…Similar to our findings, several previous reports had demonstrated that an elevated expression of VASH1 predicted a worse clinical outcome in patients with cancer [54], [55], [56], [57], [58], [59]. In various experimental disease models including those of cancer and diabetic nephropathy, the administration of adenoviral vectors encoding VASH1 resulted in therapeutic effects [19], [21], [22], [23], [24], [25], [26], [60]. More recent findings have demonstrated the role of VASH1 in enhancing the stress resistance of endothelial cells [20].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to our findings, several previous reports had demonstrated that an elevated expression of VASH1 predicted a worse clinical outcome in patients with cancer [54], [55], [56], [57], [58], [59]. In various experimental disease models including those of cancer and diabetic nephropathy, the administration of adenoviral vectors encoding VASH1 resulted in therapeutic effects [19], [21], [22], [23], [24], [25], [26], [60]. More recent findings have demonstrated the role of VASH1 in enhancing the stress resistance of endothelial cells [20].…”
Section: Discussionsupporting
confidence: 91%
“…However, the cell surface receptor(s) for VASH1 have not yet been identified. The therapeutic efficacy of VASH1 against tumor growth and atherosclerosis models has been reported [19], [21], [22], [23], [24]. We previously reported the therapeutic effects of the adenoviral transfer of human VASH1 in mouse type 1 and 2 diabetic nephropathy models [25], [26].…”
Section: Introductionmentioning
confidence: 93%
“…Watanabe et al (2004) proposed that VASH1 is an endothelium-derived negative feedback regulator of angiogenesis. VASH1 has been reported to be expressed predominantly in the endothelial cells of the artery, corneal, retina, lymph node, endometrium, glomerulus, and tumors in humans , Yoshinaga et al 2008, Hosaka et al 2009, Tamaki et al 2009) and mice , Heishi et al 2010, Li et al 2010. Expression studies in human endothelial cells revealed that VASH1 protein localized to the nucleus and cytoplasm (Watanabe et al 2004, Kern et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, VASH1 is not only expressed in normal tissue, but VASH1 expression in vascular ECs around malignant tumors has also been documented in various carcinomas. In addition to expression in malignant tumors, the relationship to prognosis, tumor growth, metastasis, and more has been examined; VASH1 is gaining attention as a new target or biomarker for predicting prognosis (Li et al 2010;Chan et al 2012;Coch et al 2014). For example, current studies report cases of poor prognosis having high expression of VASH1 in breast carcinoma and non-small cell lung carcinoma (NSCLC) (Hosaka et al 2009;Tamaki et al 2009).…”
Section: Introductionmentioning
confidence: 99%